THE INFLUENCE OF FINANCIAL LITERACY, FINANCIALINCLUSION, AND FINTECH ON THE FINANCIAL BEHAVIOR OF MSMES IN SUNGAI PENUH CITY - Endah Sri Wahyuni; Bustami Bustami; Eva Sumanti; Elvi Nilda; Samsul Bahry Harahap; Azhar Azhar (CV Visionary Raya Sakti, 2026)
Research Objectives: This study aims to analyze the influence of financial literacy, financial inclusion, and financial technology (fintech) on the financial behavior of Micro, Small, and Medium Enterprises (MSMEs) in Sungai Penuh City. It also seeks to examine the simultaneous effects of these variables and identify the dominant factor influencing MSMEs’ financial behavior. Design/ Methodology / Approach Research: The study adopts a quantitative associative research design. The population consists of 30 MSMEs in Sungai Penuh City, all of which are selected as the sample using a simple random sampling technique. Data are collected through structured questionnaires using a five-point Likert scale. The research instruments are tested for validity and reliability. The data analysis techniques include: Classical assumption tests (normality, multicollinearity, heteroscedasticity) , Multiple linear regression analysis, Hypothesis testing using t-test and F-test, Coefficient of determination (R²) analysis, Statistical analysis is conducted using SPSS software. Research Results: The findings reveal that:Financial literacy has a positive and significant effect on MSMEs’ financial behavior, making it the most influential variable, Financial inclusion has a negative and insignificant effect, indicating that access to financial services does not necessarily translate into improved financial behavior, Fintech also shows a negative and insignificant effect, suggesting limited adoption and utilization among MSMEs, Simultaneously, financial literacy, financial inclusion, and fintech significantly influence financial behavior, as indicated by the F-test, The explanatory power of the model is relatively weak (R² = 28.7%), implying that other external factors also play a substantial role in shaping financial behavior. ​Implications of Research Results: The study implies that improving MSMEs’ financial behavior should primarily focus on enhancing financial literacy, as it is the key determinant of effective financial management. Additionally: There is a need to strengthen financial education and training programs for MSME actors, Efforts should be made to increase awareness and practical utilization of financial inclusion services, Policymakers and financial institutions should promote user-friendly and accessible fintech solutions, accompanied by education and mentoring, The findings also suggest that future research should incorporate additional variables, such as psychological factors, business experience, and policy support, to better explain MSMEs’ financial behavior.